When acute adversity improves psychological health: A social-contextual framework - Mancini, Anthony D (Psychological review, 2019)
Human beings are routinely exposed to varying forms of acute adversity. Our responses take varying forms too, ranging from chronic distress to resilience. Although this pronounced variability is widely recognized, one possible outcome of acute adversity has been invariably, though understandably, ignored: an in psychological and social functioning. In this analysis, I argue that, under some conditions, people can experience marked psychological improvement after acute adversity. I describe this response pattern as (PGA) and define it as favorable and reliable change on an index of psychological functioning from before to after exposure to adversity. In the present article, first I distinguish PGA from traditional perspectives on growth after adversity on the basis of key conceptual differences. I then review empirical evidence for PGA as a replicable response pattern following different forms of adversity, including bereavement, military deployment, and mass trauma. I propose a multilevel theoretical model for PGA that focuses on automatic prosocial affiliative behaviors and group-level contextual factors that are conditioned by acute adversity. I describe moderators and boundary conditions at different levels of analysis that will enhance or detract from the likelihood of PGA. I conclude with the implications of PGA for theory and empirical research on postadversity outcomes and outline a research agenda to better understand it. (PsycINFO Database Record (c) 2019 APA, all rights reserved).